Dispositional mindfulness and psychological well-being: investigating the mediating role of meaning in life - Aldbyani, Aamer; Wang, Guiyun; Chuanxia, Zhang; Qi, Yanxia; Li, Jiaojiao; Leng, Jie (Frontiers in Psychology, 2025)
IntroductionMindfulness has been widely recognized for its positive impact on various aspects of psychological well-being. Prior research has investigated the role of mindfulness in enhancing hope and life satisfaction as separate constructs. However, limited attention has been given to the simultaneous influence of mindfulness on both hope and life satisfaction and the underlying mechanisms that may explain these relationships. This study examines the role of dispositional mindfulness in fostering hope and life satisfaction concurrently and explores the potential mediating role of meaning in life in this relationship.MethodsA total of 1,766 Chinese college students from Shandong Xiehe University participated in the study. Participants completed the Mindful Attention Awareness Scale (MAAS) to assess dispositional mindfulness, the Adult Hope Scale (AHS) to measure hope, the Satisfaction with Life Scale (SWLS) to evaluate life satisfaction, and the Meaning in Life Questionnaire (MLQ) to assess their perceived meaning in life. Statistical analyses, including mediation analysis, were conducted to explore the relationships among these variables.ResultsThe findings indicated that meaning in life partially mediated the relationship between dispositional mindfulness and both hope and life satisfaction. Specifically, higher levels of dispositional mindfulness were associated with greater hope and life satisfaction, and this relationship was partially explained by increased perceptions of meaning in life.DiscussionThese results underscore the critical role of meaning in life as a mediator in the positive effects of mindfulness on psychological well-being. The findings suggest that interventions aimed at enhancing mindfulness may benefit from incorporating strategies to foster meaning in life, thereby amplifying their impact on hope and life satisfaction. This study advances our understanding of the mechanisms linking mindfulness to key indicators of psychological well-being and highlights the integrative role of meaning in life in these processes.